GUIDED INQUIRY LEARNING MODEL: A STRATEGY TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS' SCIENCE PROCESS SKILLS - Boling, Theresia Exanthi; Fauziah, An Nuril Maulida (PT. Jurnal Center Indonesia Publisher, 2025)
Science learning is very important in producing quality students, related to the nature of science. In the learning process, we must view science not only as a product such as facts, concepts, theories, or laws, but also as scientific skills and attitudes. Mastery of science process skills (KPS) is much more crucial than just memorizing, because KPS gives students the opportunity to discover and develop facts and concepts, while building attitudes and values through the experiences they experience. KPS is a basic competency that is the main driver in supporting the discovery, development and mastery of scientific concepts by students. This research aims to determine the effect of the guided inquiry model as a solution to improve students' science process skills at one of the state junior high schools in Surabaya. This research uses a pre-experimental type of research and a One Group Pretest – Posttest research design. The research results show that the guided inquiry learning model has a positive effect on improving junior high school students' science process skills with an n-gain of 0.55 which is in the medium category